Feasibility of Zakat-based Crowdfunding for Marginalized Farmers in Bangladesh - Chowdhury, Chandrima (My University, 2023)
The arrangement of funds and financing for the agriculture sector in Bangladesh is still considered in crisis that is coupled with concurrent uncertain situations like population growth and natural disasters. Therefore, specific financial terms such as Zakat that are based on and practiced in Islam, the religious origination of the major-ity of Bangladeshi, at the same time highly appreciated and carried out by other countries are found well complementary to agricultural project financing. The pur-pose of this study is to explore the feasibility of using zakat-based crowdfunding as a means of supporting marginalized farmers in Bangladesh. This study employs a case study approach, using secondary data sources to conduct a thematic analysis of za-kat-based crowdfunding for marginalized farmers. The findings of the study indicate that zakat-based crowdfunding can be a viable solution to support marginalized farmers in Bangladesh. The relevance of the study is in place due to the urgency to solve the problems of agricultural financing in Bangladesh. The study recommends the establishment of a zakat-based crowdfunding platform that caters specifically to the needs of marginalized farmers in Bangladesh. However, the study also identifies some limitations, such as the lack of primary data and the context of generalizability. Despite these limitations, the study concludes that zakat-based crowdfunding can effectively support marginalized farmers in Bangladesh, and further research in this area is warranted.
Keywords: Agricultural Finance, Zakat, Crowdfunding, Microfinance, Marginal Farmers, Thematic Analysis, Financial Inclusion